Hollywood's indies : classic divisions, specialty labels and the American film market / Yannis Tzioumakis - Tzioumakis, Yannis
For over three decades the major Hollywood studios have operated specialty film divisions, companies that were originally established to focus primarily on the European arthouse film market, before moving on to the burgeoning American independent film market and in the process transforming it in fundamental ways. Hollywood's Indies is the first book to offer an in depth examination of the phenomenon of the studio specialty film labels, by tracing their history since the establishment of the first such division in 1980, United Artists Classics. The book provides a detailed account of these divi.